Modeling of Energy Release at the Final Stage of the Meteoroid Movement - Egorova Lidia A.; Lokhin Valery V. (Open Astronomy, 2016)
The paper continues to build upon the author’s previous research on fireballs fragmentation. A model of the sudden explosive destruction of the cosmic body at the height of the maximum flash is used. After the fragmentation, the kinetic energy of the moving particles of a meteoroid passes into the thermal energy of the gas volume inwhich their motion takes place. The temperature of a gas cloud calculated analytically using energy conservation lawand equations of physical theory of meteors. The mass distribution of fragments was taken from the literature. The high temperature of the gas in a cloud allows us to talk about the phenomenon of a "thermal explosion".